How Film Affects English Language Learning Instruction - Shivan khudhur Dizayee (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The teaching and learning of English as a second language or a foreign linguistic communication is practised in many non-English speaking countries globally. Special English teaching centres have been built in these states to facilitate English language reading and instruction. The centres focus mainly on the teaching and learning of the English language through the skills of reading and writing. Novel methods of teaching English using the latest technology has been embraced by many learning centres and using film adaptations are one among them. Films being excellent sources of literature and language, teaching English language can be made more interesting and efficient by the use of films which provide the students with ample opportunities and facilities for learning. The main lacunae in the learning procedure, nevertheless, is the immense array of words in English, the unfamiliar background of the students, difficulty in comprehending the words and phrases, the communication gap between teachers and pupils, and the numerous choices in the movie versions. The main objective of the current study is to investigate the perspectives of the students on the effect of using film adaptations in learninglaguage, to assess the efficacy of the film adaptations as tools in teaching literature with respect to the students. The survey was taken utilizing a questionnaire directed to measure the posture of the students in using the motion picture adaptations. The results evaluated in the study were of two types, e.g., results directly abstracted from the questionnaire and results that are evaluated based on the statistical formula applied over it to retain the actual trends in the feedback collected from the respondents in the field survey. It is evident from the current study that the students are greatly benefitted by viewing the film adaptations since films provided effective teaching and learning methods and enhanced the individual skills of speaking, listening, reading and writing. However, the small sample size, and the study being confined to a small population, generalizations are not possible.